A light-absorbing film and its preparation method and application

Preparation of copper-vanasulfur or copper-vanase selenium films by solution method solves the problems of scarce, harmful defects, high preparation cost and low photoelectric conversion efficiency of existing copper-based thin-film solar cells, and achieves high-efficiency and low-cost film preparation and high photoelectric conversion efficiency.

CN117995930BActive Publication Date: 2025-02-07INNER MONGOLIA NORMAL UNIVERSITY

Patent Information

Application Number
CN202410086924.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-22
Publication Date
2025-02-07
Estimated Expiration
2044-01-22

AI Technical Summary

Technical Problem

Existing copper-based thin-film solar cells face problems such as scarce constituent elements, prone to harmful defects, high preparation costs, low photoelectric conversion efficiency and high density heterogeneous phases.

Method used

The solution method is used to prepare copper-vanasulfur film, copper-vanasulfur-selenium film or copper-vanasulfur-selenium film. By adjusting the element ratio in the amine-thiol solution system, the element ratio in the light-absorbing film is accurately controlled to reduce the generation of miscellaneous phases.

Benefits of technology

The high-purity copper-vanasulfur or copper-vanasulfur films are prepared in a low-cost and simple operational manner, which improves the photoelectric conversion efficiency of solar cells and reduces the generation of miscellaneous phases.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117995930B_ABST
    Figure CN117995930B_ABST
Patent Text Reader

Abstract

The present invention proposes a light-absorbing film and a preparation method and application thereof, including a preparation method of a copper-vanadium-sulfur / copper-vanadium-selenium / copper-vanadium-sulfur-selenium light-absorbing film based on a solution method, and an application of the light-absorbing film prepared by the method on a solar cell. The preparation method is simple to operate and low in cost. Thioglycolic acid and ethanolamine are used as ligands, and ethylene glycol methyl ether is used as a solvent to adjust the viscosity to prepare a precursor solution; a copper-vanadium-sulfur / copper-vanadium-selenium / copper-vanadium-sulfur-selenium film is prepared by spin coating-sintering mode and adjusting the feed ratio of elements; high-temperature heat treatment is continued for sulfurization / selenization reaction to obtain a large-grain through-type copper-vanadium-sulfur / copper-vanadium-selenium / copper-vanadium-sulfur-selenium film, which can avoid the generation of impurities in the film, and the prepared light-absorbing film is applied to the light-absorbing layer of a solar cell, which is conducive to assembling a copper-vanadium-sulfur-selenium thin film solar cell with high photoelectric conversion efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical field:

[0001] The invention belongs to the technical field of solar cells, and in particular relates to a light-absorbing film and a preparation method and application thereof. Background technology:

[0002] As part of the third generation of solar cells, inorganic compound thin film solar cells represented by cadmium telluride (CdTe) and copper indium gallium selenide (Cu(In,Ga)Se2, CIGS for short) are developing extremely rapidly. The highest photoelectric conversion efficiency of CdTe and CIGS thin film solar cells has exceeded 23%. This impressive achievement symbolizes the great application prospects of inorganic compound thin film solar cells and also establishes the important position of inorganic compound thin film solar cells in the field of new energy. However, the toxicity of cadmium (Cd) and the scarcity of indium (In), gallium (Ga) and tellurium (Te) limit their practical applications in the future. To this end, scientific researchers have taken many effective measures: one idea is to use trivalent antimony ions (Sb 3+ ) to replace the original trivalent indium ion (In 3+ ), forming copper antimony sulfur (CuSbS2) material, but the performance of its corresponding thin film solar cell has high requirements on the preparation method and process of the thin film absorption layer, resulting in high preparation cost of the battery; another idea is to use a divalent zinc ion (Zn 2+ ) and a tetravalent tin ion (Sn 4+ ) replaces two In in the CIGS unit cell 3+ (Ga 3+ ) ions to form copper zinc tin sulfur selenium (Cu2ZnSn(S,Se)4, referred to as CZTSSe) material, which has the characteristics of rich content of constituent elements in the earth's crust, low toxicity, environmental protection, strong sustainability, and is suitable for long-term development. However, due to the zinc ion (Zn 2+ )'s radius and copper ions (Cu + )'s radius Extremely close, Cu is easily produced Zn Due to harmful defects such as carbon dioxide, its photoelectric conversion efficiency has been at a bottleneck period, and it is difficult to achieve a major breakthrough. Based on the above difficulties faced by inorganic compound thin film solar energy, people have to continue to explore new photovoltaic materials with rich content of earth's crust, environmental protection and sustainable development.

[0003] Recently, researchers have proposed using a monovalent Cu + and a pentavalent metal ion M that is abundant in the earth's crust, low in toxicity and environmentally friendly 5+ (For example: vanadium (V 5+ ), niobium (Nb 5+ ), Tantalum 5+) etc.) to replace Zn in the CZTSSe unit cell 2+ and Sn 4+ , forming a new type of Cu3MCh4 (M=V,Nb,Ta;Ch=S,Se,Te) material. Theoretical calculations show that they are all P-type semiconductor materials with optical band gaps below 3.0eV, which are suitable for a variety of optoelectronic devices. Among them, Cu3VCh4 (Ch=S,Se) material has the advantages of a band gap below 1.5eV, high absorption coefficient, high mobility, etc., and is more suitable as a light-absorbing layer for solar cells.

[0004] However, at present, the research on Cu3VCh4 (Ch=S,Se) materials is focused on the synthesis and theoretical calculation of materials. For the research on the application in the field of solar cells, only Lin et al. used the co-sputtering method to prepare a copper-vanadium-sulfur solar cell with a photoelectric conversion efficiency of 3.11%, and faced the dilemma of high-density impurities (Cu2S, CuS). In addition, the magnetron sputtering method is based on expensive vacuum equipment, and the use of vacuum equipment will increase the preparation cost of solar cells, which is not conducive to the subsequent long-term development of such solar cells. Summary of the invention:

[0005] The first purpose of the present invention is to provide a method for preparing a light-absorbing film in order to address the problems faced by existing copper-based thin-film solar cells, such as the scarcity of constituent elements and the easy generation of harmful defects, as well as the high cost, low photoelectric conversion efficiency, and high-density impurities of copper-vanadium-sulfur solar cells prepared by the co-sputtering method. The method can prepare copper-vanadium-sulfur thin films, copper-vanadium-selenium thin films, and copper-vanadium-sulfur-selenium thin films by a solution method, and the method is simple and low in cost.

[0006] The second object of the present invention is to provide a copper-vanadium-sulfur film or a copper-vanadium-selenium film or a copper-vanadium-sulfur-selenium film with less impurities and high purity.

[0007] The third object of the present invention is to provide an application of a copper-vanadium-sulfur film or a copper-vanadium-selenium film or a copper-vanadium-sulfur-selenium film in preparing a light-absorbing layer of a solar cell, and the prepared solar cell has a high photoelectric conversion efficiency.

[0008] The first object of the present invention is implemented by the following technical solutions:

[0009] A method for preparing a light-absorbing film comprises the following steps:

[0010] Step A: using thioglycolic acid and ethanolamine as ligands, adding thioglycolic acid and ethanolamine into a reaction container, and reacting to obtain a molecular solution;

[0011] Step B: adding a copper source and a vanadium source to the molecular solution prepared in step A, reacting until the copper source and the vanadium source are completely dissolved to obtain a mixed solution;

[0012] Step C: adding a sulfur source and / or a selenium source to the mixed solution prepared in step B, and adding ethylene glycol methyl ether as a solvent to adjust the viscosity, reacting until the sulfur source and / or the selenium source are completely dissolved, and then centrifuging to obtain a supernatant, which is a copper vanadium sulfur precursor solution or a copper vanadium selenium precursor solution or a copper vanadium sulfur selenium precursor solution;

[0013] Step D: spin coating and sintering the copper-vanadium-sulfur precursor solution or the copper-vanadium-selenium precursor solution or the copper-vanadium-sulfur-selenium precursor solution prepared in step C to obtain a copper-vanadium-sulfur thin film, a copper-vanadium-selenium thin film or a copper-vanadium-sulfur-selenium thin film.

[0014] Furthermore, in step A, the volume ratio of the thioglycolic acid to the ethanolamine is (1-3):(1-4); the reaction temperature is 60-100° C., and the reaction time is 10-60 min.

[0015] Furthermore, in step B, the copper source is one or more of elemental copper, copper salt, copper oxide, cuprous oxide, and copper acetate; the vanadium source is one or more of vanadium acetylacetonate and vanadium pentoxide; the reaction temperature is 60-100° C., and the reaction time is 10-60 min.

[0016] Furthermore, in step C, the sulfur source is one or more of thiourea and sulfur powder; the selenium source is one or more of selenium powder, selenium granules, and selenium dioxide; the reaction temperature is room temperature to 80°C, and the reaction time is 30 to 120 minutes; the volume ratio of the ethylene glycol methyl ether to the thioglycolic acid and the ethanolamine is (3 to 7): (1 to 3): (1 to 4).

[0017] Furthermore, in the step D, the sintering temperature is 300-340° C., and the time is 1.5-6 min; the spin coating and sintering process are repeated 4-10 times.

[0018] Furthermore, the copper-vanadium-sulfur film, the copper-vanadium-selenium film or the copper-vanadium-sulfur-selenium film prepared in step D is subjected to secondary sintering; the secondary sintering temperature is 350-450° C. and the time is 10-30 min.

[0019] Furthermore, the method further comprises step E: adding a sulfur source and / or a selenium source to the copper-vanadium-sulfur thin film, the copper-vanadium-selenium thin film or the copper-vanadium-sulfur-selenium thin film obtained in step D to carry out a sulfurization and / or selenization reaction to obtain a large-grain through-type copper-vanadium-sulfur thin film, a large-grain through-type copper-vanadium-selenium thin film or a large-grain through-type copper-vanadium-sulfur-selenium thin film. A sulfur source is added to the copper-vanadium-sulfur film for sulfurization reaction to obtain a copper-vanadium-sulfur film with large grains penetrating, a selenium source is added to the copper-vanadium-sulfur film for selenization reaction to obtain a copper-vanadium-sulfur-selenium film with large grains penetrating, a sulfur source and a selenium source are added to the copper-vanadium-sulfur film for sulfurization and selenization reaction to obtain a copper-vanadium-sulfur-selenium film with large grains penetrating; a selenium source is added to the copper-vanadium-selenium film for selenization reaction to obtain a copper-vanadium-selenium film with large grains penetrating, a sulfur source is added to the copper-vanadium-selenium film for sulfurization reaction to obtain a copper-vanadium-sulfur-selenium film with large grains penetrating, a sulfur source and a selenium source are added to the copper-vanadium-selenium film for sulfurization and selenization reaction to obtain a copper-vanadium-sulfur-selenium film with large grains penetrating; a sulfur source and / or a selenium source can be added to the copper-vanadium-sulfur-selenium film for sulfurization reaction and / or selenization reaction to affect the sulfur / selenium ratio in the final copper-vanadium-sulfur-selenium film with large grains penetrating.

[0020] Furthermore, in the step E, the temperature of the sulfidation reaction or the selenization reaction is 350-560° C., and the reaction time is 10-90 min. In the step E, the sulfur source is one or more of sulfur powder, hydrogen sulfide, and thiourea, and the selenium source is one or more of selenium powder, selenium particles, selenium dioxide, and selenium disulfide.

[0021] Furthermore, in the step E, the sulfurization reaction is a one-step sulfurization method, a two-step sulfurization method, or a three-step sulfurization method; the selenization reaction is a one-step selenization method, a two-step selenization method, or a three-step selenization method. This helps to improve the photoelectric conversion efficiency of solar cells using large-grain through-type copper-vanadium-sulfur thin films, copper-vanadium-selenium thin films, or copper-vanadium-sulfur-selenium thin films.

[0022] The second object of the present invention is implemented by the following technical solutions:

[0023] The copper-vanadium-sulfur thin film or the copper-vanadium-selenium thin film or the copper-vanadium-sulfur-selenium thin film prepared by the above light-absorbing thin film preparation method.

[0024] The third object of the present invention is implemented by the following technical solutions:

[0025] Application of the copper-vanadium-sulfur film or copper-vanadium-selenium film or copper-vanadium-sulfur-selenium film in preparing the light-absorbing layer of a solar cell.

[0026] Advantages of the present invention:

[0027] As mentioned in the background technology, the Cu3VCh4 prepared by the current method has the problems of low photoelectric conversion efficiency, high density impurity phase, high preparation cost, etc. The present invention adopts an amine-thiol solution system to prepare a copper vanadium sulfur selenium solar cell, which has the following advantages:

[0028] First, the preparation method is easy to operate and low in cost. A copper-vanadium-sulfur thin film or a copper-vanadium-selenium thin film or a copper-vanadium-sulfur-selenium thin film can be prepared by adding a sulfur source and / or a selenium source for sulfurization and / or selenization reaction. Second, the amine-thiol mixed solution can directly dissolve the copper source, vanadium source, sulfur source and selenium source, so that the ratio of elements in the light-absorbing thin film can be precisely controlled by adjusting the ratio of each solute, thereby avoiding the generation of impurities in the thin film. Third, the light-absorbing thin film prepared by this method can be used to assemble copper-vanadium-sulfur or copper-vanadium-selenium or copper-vanadium-sulfur-selenium thin film solar cells, which is beneficial to improving the photoelectric conversion efficiency of solar cells. Description of the drawings:

[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0030] Figure 1 This is a photo of the copper vanadium selenium precursor solution prepared in Example 1;

[0031] Figure 2 is a SEM image of the copper-vanadium-sulfur film prepared in Example 2;

[0032] Figure 3 This is a SEM image of the large-grain through-type copper-vanadium-selenium thin film prepared in Example 4;

[0033] Figure 4 This is a SEM image of the large-grain through-type copper-vanadium-selenium thin film prepared in Example 5;

[0034] Figure 5 This is the UV-visible absorption spectrum of the large-grain through-type copper vanadium selenide thin film prepared in Example 5;

[0035] Figure 6 This is the XRD pattern of the large-grain through-type copper-vanadium-sulfur-selenium thin film prepared in Example 6;

[0036] Figure 7 This is a SEM image of the large-grain through-type copper-vanadium-selenium thin film prepared in Example 7;

[0037] Figure 8 XRD diagrams of large-grain through-type copper-vanadium-sulfur-selenium thin films with different Cu / V ratios in Example 9;

[0038] Fig. 9 is a JV curve diagram of the solar cell assembled in Example 10;

[0039] Fig.10 It is a JV curve diagram of the assembled solar cell of Example 11.

[0040] Fig.11 is an EQE curve diagram of the assembled solar cell of Example 11;

[0041] Fig.12 is a JV curve diagram of the solar cell assembled in Example 12;

[0042] Fig.13 This is a JV curve diagram of the assembled solar cell of Example 13. Specific implementation method:

[0043] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0044] Example 1

[0045] A method for preparing a copper vanadium selenium (CVSe) precursor solution comprises the following steps:

[0046] Step A: Add 2 mL of thioglycolic acid and 3 mL of ethanolamine into a conical flask, stir on a magnetic stirrer at 70°C for 30 min to obtain a molecular solution;

[0047] Step B: adding 178 mg of copper and 259.8 mg of vanadyl acetylacetonate to the molecular solution prepared in step A, and continuing to stir the reaction on a magnetic stirrer at 70° C. for 40 min until the copper and vanadyl acetylacetonate are completely dissolved to obtain a mixed solution;

[0048] Step C: Add 200 mg of selenium powder and 7 mL of ethylene glycol methyl ether to the mixed solution prepared in step B, continue stirring the reaction on a magnetic stirrer at 70° C. for 60 min, and then centrifuge in a high-speed centrifuge at a speed of 3000 r / min for 5 min to obtain a uniform copper vanadium selenium precursor solution free of impurities.

[0049] The copper vanadium selenium precursor solution prepared in the above steps is as follows Figure 1 shown.

[0050] Example 2

[0051] A method for preparing a copper vanadium sulfur (CVS) light-absorbing film comprises the following steps:

[0052] Step A: Add 1 mL of thioglycolic acid and 2 mL of ethanolamine into a conical flask, stir on a magnetic stirrer at 100°C for 30 min to obtain a molecular solution;

[0053] Step B: 598.6 mg of copper acetate and 259.8 mg of vanadyl acetylacetonate in the molecular solution prepared in step A are stirred on a magnetic stirrer at 100° C. for 20 min until the copper acetate and vanadyl acetylacetonate are completely dissolved to obtain a mixed solution;

[0054] Step C: After the mixed solution prepared in step B is cooled to room temperature, 301.4 mg of sulfur powder and 4 mL of ethylene glycol methyl ether are added, and the mixture is reacted for 90 min at room temperature, and then centrifuged in a high-speed centrifuge at a speed of 3000 r / min for 5 min to obtain a uniform copper vanadium sulfur precursor solution free of impurities;

[0055] Step D: Spin-coat the copper-vanadium-sulfur precursor solution prepared in step C on a coater, and then sinter on a heating table at 320° C. for 2.5 min. Repeat the above spin-coating-sintering steps 5 times to obtain a copper-vanadium-sulfur thin film.

[0056] The scanning electron microscope (SEM) image of the copper-vanadium-sulfur film prepared in the above steps is as follows: Figure 2 As shown, (a) is the surface morphology of the film, (b) is the cross-sectional morphology of the film, the lower part of (b) is the Mo back electrode, and the layered structure on the upper part is the prepared film.

[0057] Example 3

[0058] A method for preparing a large-grain through-type copper-vanadium-sulfur (CVS) light-absorbing film comprises the following steps:

[0059] Step A: Add 1 mL of thioglycolic acid and 2 mL of ethanolamine to a conical flask and react in a 70°C water bath for 30 min. A molecular solution is obtained;

[0060] Step B: Add 216 mg of copper oxide and 259.8 mg of vanadyl acetylacetonate to the molecular solution prepared in step A, and react in a 70° C. water bath for 60 min until the copper oxide and vanadyl acetylacetonate are completely dissolved to obtain a mixed solution;

[0061] Step C: After cooling the mixed solution prepared in step B, 301.4 mg of thiourea and 4 mL of ethylene glycol methyl ether were added, and the mixture was dissolved for 90 min at room temperature, and then centrifuged in a high-speed centrifuge at a speed of 3000 r / min for 5 min to obtain a uniform copper vanadium sulfur precursor solution free of impurities;

[0062] Step D: Spin coating the copper-vanadium-sulfur precursor solution prepared in step C on a spin coater, sintering on a heating table at 300° C. for 2.5 min, and repeating the above spin coating-sintering steps 7 times to obtain a copper-vanadium-sulfur thin film;

[0063] Step E: Add hydrogen sulfide to the copper-vanadium-sulfur film obtained in step D for sulfidation reaction. Under the condition of a mixed atmosphere of nitrogen and hydrogen sulfide, the temperature of the sulfidation equipment is raised from room temperature to 530°C and kept warm for 30 minutes to obtain a large-grain through-type copper-vanadium-sulfur film. Compared with Example 2 in which no sulfidation reaction is performed, the copper-vanadium-sulfur film of this embodiment shows a state of large-grain coverage and penetration.

[0064] Example 4

[0065] A method for preparing a large-grain through-type copper vanadium selenium (CVSe) light-absorbing film comprises the following steps:

[0066] Step A: Add 2 mL of thioglycolic acid and 3 mL of ethanolamine into a conical flask and react in a 70°C water bath for 30 min to obtain a molecular solution;

[0067] Step B: Add 558.7 mg of copper acetate and 259.8 mg of vanadyl acetylacetonate to the molecular solution prepared in step A, adjust the temperature to 80° C. and continue the reaction for 30 min until the copper acetate and vanadyl acetylacetonate are completely dissolved to obtain a mixed solution;

[0068] Step C: Add 200 mg of selenium powder and 7 mL of ethylene glycol methyl ether to the mixed solution prepared in step B, continue the reaction at 80° C. for 90 min, and then centrifuge in a high-speed centrifuge at a speed of 3000 r / min for 5 min to obtain a uniform copper vanadium selenium precursor solution free of impurities;

[0069] Step D: Spin coating the copper vanadium selenium precursor solution prepared in step C on a spin coater, sintering on a heating table at 340° C. for 1 min, and repeating the above spin coating-sintering steps 8 times to obtain a copper vanadium selenium thin film;

[0070] Step E: Add selenium powder to the copper vanadium selenide film obtained in step D for selenization reaction, using a one-step selenization process, that is: in a nitrogen atmosphere, place 350 mg of selenium powder, increase the temperature of the selenization equipment from room temperature to 530°C in one step, and keep it warm for 20 minutes to obtain a large-grain through-type copper vanadium selenide film.

[0071] The top view SEM image of the large grain through-type copper vanadium selenide film prepared by the above method is as follows: Figure 3 shown.

[0072] Example 5

[0073] A method for preparing a large-grain through-type copper vanadium selenium (CVSe) light-absorbing film comprises the following steps:

[0074] Step A: Add 3 mL of thioglycolic acid and 3 mL of ethanolamine into a conical flask and stir on a magnetic stirrer at 70°C for 30 min to obtain a molecular solution;

[0075] Step B: Add 178 mg of single copper and 182 mg of vanadium pentoxide to the molecular solution prepared in step A, and continue to stir the reaction on a magnetic stirrer at 70° C. for 40 min until the copper source and the vanadium source are completely dissolved to obtain a mixed solution;

[0076] Step C: Add 400 mg of selenium powder and 7 mL of ethylene glycol methyl ether to the mixed solution prepared in step B, continue to react on a magnetic stirrer at 70° C. for 60 min until the selenium powder is completely dissolved, and then centrifuge in a high-speed centrifuge at a speed of 4000 r / min for 5 min to obtain a uniform copper vanadium selenium precursor solution free of impurities;

[0077] Step D: Spin-coating the copper vanadium selenide precursor solution prepared in step C on a coating machine and sintering on a heating table at 340° C. to obtain a copper vanadium selenide film, and then sintering the copper vanadium selenide film for a second time in air at a sintering temperature of 350° C. for 20 min;

[0078] Step E: Add selenium powder to the copper vanadium selenide film after secondary sintering obtained in step D for selenization reaction, using a one-step selenization process, that is: in a nitrogen atmosphere, with 350 mg of selenium powder placed, the temperature of the selenization equipment is increased from room temperature to 530°C in one step, and kept warm for 20 minutes to obtain a large-grain through-type copper vanadium selenide film.

[0079] The thin film prepared by the above steps has a layer of small particles that disappears and is completely transformed into a thin film with large particles penetrating through it. The SEM image of its side cross-section is as follows: Figure 4 As shown; the film has good absorbance in the wavelength range of 400 to 800 nm, and its UV-visible absorption spectrum is shown in Figure 5 .

[0080] Example 6

[0081] A method for preparing a large-grain through-type copper vanadium sulfur selenium (CVSSe) light-absorbing film comprises the following steps:

[0082] Step A: Add 2 mL of thioglycolic acid and 3 mL of ethanolamine into a conical flask and react in a 70°C water bath for 30 min to obtain a molecular solution;

[0083] Step B: Add 558.7 mg of copper acetate and 259.8 mg of vanadyl acetylacetonate to the molecular solution prepared in step A, adjust the temperature to 80° C. and continue the reaction for 30 min until the copper source and the vanadium source are completely dissolved to obtain a mixed solution;

[0084] Step C: Add 100 mg of sulfur powder, 300 mg of selenium powder, and 9 mL of ethylene glycol methyl ether to the mixed solution prepared in step B, continue the reaction at 80° C. for 30 min until the sulfur powder and selenium powder are completely dissolved, and centrifuge at 4000 r / min for 3 min to obtain a uniform copper vanadium sulfur-selenium precursor solution free of impurities;

[0085] Step D: Spin-coat the copper-vanadium-sulfur-selenium precursor solution prepared in step C on a coater, sinter on a 300° C. heating table for 2 min, and repeat the above spin-coating-sintering steps 5 times to obtain a copper-vanadium-sulfur-selenium thin film;

[0086] Step E: Add selenium powder and a sulfur source to the copper-vanadium-sulfur-selenium film obtained in step D for sulfidation and selenization reaction to obtain a copper-vanadium-sulfur-selenium film with large grains. The selenization treatment is carried out by a one-step selenization method, that is, in a nitrogen atmosphere, 350 mg of selenium powder is placed, and the temperature of the selenization equipment is raised from room temperature to 510° C. for 40 minutes to obtain a copper-vanadium-sulfur-selenium film with large grains.

[0087] The XRD pattern of the large-grain through-type copper-vanadium-sulfur-selenium film prepared by the above method is as follows: Figure 6 As shown, the diffraction peaks in the figure all belong to copper, vanadium, sulfur and selenium.

[0088] Example 7

[0089] A method for preparing a large-grain through-type copper vanadium sulfur selenium (CVSSe) light-absorbing film comprises the following steps:

[0090] Step A: Add 2 mL of thioglycolic acid and 3 mL of ethanolamine into a conical flask and stir on a magnetic stirrer at 70°C for 30 min to obtain a molecular solution;

[0091] Step B: Add 558.7 mg of copper acetate and 259.8 mg of vanadyl acetylacetonate to the molecular solution prepared in step A, and continue to stir the reaction on a magnetic stirrer at 70° C. for 30 min until the copper acetate and vanadyl acetylacetonate are completely dissolved to obtain a mixed solution;

[0092] Step C: Cool the mixed solution prepared in step B to room temperature, add 300 mg of selenium powder, 301.4 mg of thiourea and 7 ml of ethylene glycol methyl ether, continue to react at 70° C. for 90 min until the selenium powder and thiourea are completely dissolved, and centrifuge at 3000 r / min for 5 min in a high-speed centrifuge to obtain a uniform copper vanadium sulfur-selenium precursor solution free of impurities;

[0093] Step D: Spin-coat the copper-vanadium-sulfur-selenium precursor solution prepared in step C on a spin coater, sinter on a heating table at 320° C. for 2 min, and repeat the above spin-coating-sintering steps 8 times to obtain a copper-vanadium-sulfur-selenium film;

[0094] Step E: Add selenium particles to the copper vanadium sulfur selenium film obtained in step D, and carry out selenization reaction using a two-step selenization process in a nitrogen atmosphere. First, the temperature of the selenization equipment is rapidly raised from room temperature to 400°C over 2 minutes and kept warm for 10 minutes; then, after 2 minutes, the temperature is raised from 400°C to 540°C and kept warm for 40 minutes to obtain a large-grain through-type copper vanadium sulfur selenium film.

[0095] The SEM image of the large-grain through-type copper-vanadium-sulfur-selenium thin film prepared by the above steps is as follows: Figure 7 As shown in the figure, (a) is the surface morphology of the film, and (b) is the cross-sectional morphology of the film. The copper vanadium sulfur selenide film obtained by the two-step selenization method presents a large grain layer through and a very dense surface grain morphology, which will be beneficial for its application in the light absorption layer of solar cells to improve its photoelectric conversion efficiency.

[0096] Example 8

[0097] A method for preparing a large-grain through-type copper vanadium sulfur selenium (CVSSe) light-absorbing film comprises the following steps:

[0098] Step A: Add 2 mL of thioglycolic acid and 3 mL of HCl to a conical flask and stir on a magnetic stirrer at 70 °C for 30 min to obtain a molecular solution;

[0099] Step B: Add 558.7 mg of copper acetate and 259.8 mg of vanadyl acetylacetonate to the molecular solution prepared in step A, and continue to stir the reaction on a magnetic stirrer at 70° C. for 30 min until the copper acetate and vanadyl acetylacetonate are completely dissolved to obtain a mixed solution;

[0100] Step C: After the mixed solution prepared in step B is cooled to room temperature, 300 mg of selenium powder, 301.4 mg of thiourea and 7 ml of ethylene glycol methyl ether are added, and the mixture is reacted until the selenium powder and thiourea are completely dissolved, and then the mixture is reacted at 70° C. for 90 min, and then centrifuged at 3000 r / min for 5 min to obtain a uniform copper vanadium sulfur-selenium precursor solution free of impurities;

[0101] Step D: Spin-coat the copper-vanadium-sulfur-selenium precursor solution prepared in step C on a coater, sinter on a heating table at 320° C. for 2 min, and repeat the above spin-coating-sintering steps 8 times to obtain a copper-vanadium-sulfur-selenium thin film;

[0102] Step E: The copper-vanadium-sulfur-selenium film obtained in step D is selenized by a three-step selenization process in a nitrogen atmosphere with 500 mg of selenium particles placed therein: first, the temperature of the selenization equipment is rapidly raised from room temperature to 350°C after 2 minutes and kept warm for 10 minutes; then, after 2 minutes, the temperature is raised from 350°C to 400°C and kept warm for 10 minutes; finally, after 2 minutes, the temperature is raised from 400°C to 530°C and kept warm for 10 minutes, thereby obtaining a large-grain through-type copper-vanadium-sulfur-selenium film. The three-step selenization process can promote the full absorption of selenium vapor by the film, but it has relatively high requirements on the substrate of the film, especially when the film substrate is deposited with a back electrode, the three-step selenization process has strict requirements on the preparation process of the substrate.

[0103] Example 9

[0104] Referring to the preparation method of the large-grain through-type copper vanadium sulfur selenium (CVSSe) light-absorbing film of Example 6, large-grain through-type copper vanadium sulfur selenium films with different Cu / V ratios were obtained by adjusting the addition amounts of copper acetate and vanadium acetylacetonate. Figure 8 The XRD diagrams of the large-grained copper-vanadium-sulfur-selenide thin films with different Cu / V ratios are shown below. It can be seen that when the Cu / V ratio is higher than 2.9, the CuS impurity phase will appear in the film. In order to obtain a pure CuVSSe film, the Cu / V addition ratio must be controlled below 2.9.

[0105] Example 10

[0106] A solar cell, which includes glass / FTO / CuVSSe / CdS / i-ZnO / ITO / Al from top to bottom, is assembled into the light-absorbing layer of the solar cell with the large-grain through-type copper vanadium selenide thin film of Example 5. After assembly, the performance of the solar cell is tested, such as Fig. 9 As shown, its open circuit voltage (Voc) is 0.26V and short circuit current density (Jsc) is 11.74mA / cm 2 , the fill factor (FF) is 36.04% and the photoelectric conversion efficiency is 1.10%.

[0107] Embodiment 11

[0108] A solar cell, which includes glass / Mo / CuVSSe / CdS / i-ZnO / ITO / Ag from top to bottom, and the large-grain through-type copper vanadium sulfur selenium film of Example 6 is assembled into the light-absorbing layer of the solar cell. After assembly, the performance of the solar cell is tested. It should be noted that before depositing i-ZnO, the sample with "glass / Mo / CuVSSe / CdS" needs to be treated on a heating table at 300°C for 10 minutes; the assembled solar cell also needs to be placed in a room temperature environment for 3-6 hours before testing its performance. Fig.10 and Fig.11 As shown, its open circuit voltage (Voc) is 0.381V and short circuit current density (Jsc) is 23.027mA / cm 2 , the fill factor (FF) is 43.148%, the photoelectric conversion efficiency is 3.785%, and the bandgap is 1.43eV ( Fig.11 The illustration in the figure shows the bandgap width).

[0109] Example 12

[0110] A solar cell, which includes glass / Mo / CuVSSe / CdS / i-ZnO / ITO / Ag from top to bottom, is assembled into the light-absorbing layer of the solar cell with the large-grain through-type copper-vanadium-sulfur-selenium thin film of Example 7. After assembly, the performance of the solar cell is tested. Fig.12 As shown, its open circuit voltage (Voc) is 0.435V and short circuit current density (Jsc) is 22.56mA / cm 2 , the fill factor (FF) is 45.09% and the photoelectric conversion efficiency is 4.42%.

[0111] Embodiment 13

[0112] A solar cell, which includes glass / Mo / CuVSSe / CdS / i-ZnO / ITO / Ag from top to bottom, is assembled into the light-absorbing layer of the solar cell with the large-grain through-type copper-vanadium-sulfur-selenium thin film of Example 8. After assembly, the performance of the solar cell is tested. Fig.13 As shown, its open circuit voltage (Voc) is 0.439V and short circuit current density (Jsc) is 24.87mA / cm 2 , the fill factor (FF) is 46.93% and the photoelectric conversion efficiency is 5.13%.

[0113] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a light-absorbing film, characterized in that: It includes the following steps: Step A: adding thioglycolic acid and ethanolamine into a reaction container to react to obtain a molecular solution; the reaction temperature in step A is 60-100° C. and the reaction time is 10-60 min; Step B: adding a copper source and a vanadium source to the molecular solution prepared in step A, and reacting until the copper source and the vanadium source are completely dissolved to obtain a mixed solution; the reaction temperature in step B is 60-100° C., and the reaction time is 10-60 min; Step C: adding a sulfur source and / or a selenium source to the mixed solution prepared in step B, and adding ethylene glycol methyl ether, reacting until the sulfur source and / or the selenium source are completely dissolved, and then centrifuging to obtain a supernatant, which is a copper vanadium sulfur precursor solution or a copper vanadium selenium precursor solution or a copper vanadium sulfur selenium precursor solution; the volume ratio of the ethylene glycol methyl ether to the thioglycolic acid and the ethanolamine is (3-7): (1-3): (1-4); the reaction temperature in step C is room temperature to 80°C, and the reaction time is 30 to 120 minutes; Step D: spin coating and sintering the copper-vanadium-sulfur precursor solution or the copper-vanadium-selenium precursor solution or the copper-vanadium-sulfur-selenium precursor solution prepared in step C to obtain a copper-vanadium-sulfur film, a copper-vanadium-selenium film or a copper-vanadium-sulfur-selenium film; the sintering temperature is 300 to 340° C., and the time is 1.5 to 6 minutes; the spin coating and sintering process is repeated 4 to 10 times.

2. The method for preparing the light-absorbing film according to claim 1, characterized in that: In the step B, the copper source is one or more of elemental copper, copper salt, copper oxide, cuprous oxide, and copper acetate; and the vanadium source is one or more of vanadium acetylacetonate and vanadium pentoxide.

3. The method for preparing the light-absorbing film according to claim 1, characterized in that: In step C, the sulfur source is one or more of thiourea and sulfur powder; the selenium source is one or more of selenium powder, selenium particles, and selenium dioxide.

4. The method for preparing a light-absorbing film according to claim 1, characterized in that: The copper-vanadium-sulfur film, the copper-vanadium-selenium film or the copper-vanadium-sulfur-selenium film prepared in step D is subjected to secondary sintering; the secondary sintering temperature is 350-450° C. and the time is 10-30 minutes.

5. The method for preparing a light-absorbing film according to any one of claims 1 to 4, characterized in that: The method further comprises step E: adding a sulfur source and / or a selenium source to the copper-vanadium-sulfur thin film, the copper-vanadium-selenium thin film or the copper-vanadium-sulfur-selenium thin film obtained in step D to carry out a sulfurization and / or selenization reaction to obtain a large-grain through-type copper-vanadium-sulfur thin film, a large-grain through-type copper-vanadium-selenium thin film or a large-grain through-type copper-vanadium-sulfur-selenium thin film.

6. The method for preparing a light-absorbing film according to claim 5, characterized in that: In the step E, the temperature of the sulfidation reaction or the selenization reaction is 350-560° C., and the reaction time is 10-90 min. In the step E, the sulfur source is one or more of sulfur powder, hydrogen sulfide, and thiourea, and the selenium source is one or more of selenium powder, selenium particles, selenium dioxide, and selenium disulfide.

7. The method for preparing a light-absorbing film according to claim 5, characterized in that: In the step E, the vulcanization reaction is a one-step vulcanization method, a two-step vulcanization method or a three-step vulcanization method; the selenization reaction is a one-step selenization method, a two-step selenization method or a three-step selenization method.

8. A copper-vanadium-sulfur thin film, a copper-vanadium-selenium thin film or a copper-vanadium-sulfur-selenium thin film prepared by the method for preparing a light-absorbing thin film according to any one of claims 1 to 4, 6 and 7.

9. The copper-vanadium-sulfur thin film, copper-vanadium-selenium thin film or copper-vanadium-sulfur-selenium thin film prepared by the method for preparing the light-absorbing thin film according to claim 5.

10. Use of the copper-vanadium-sulfur thin film, the copper-vanadium-selenium thin film or the copper-vanadium-sulfur-selenium thin film according to claim 8 in preparing a light-absorbing layer of a solar cell.

11. Use of the copper-vanadium-sulfur thin film, the copper-vanadium-selenium thin film or the copper-vanadium-sulfur-selenium thin film according to claim 9 in preparing a light-absorbing layer of a solar cell.

Citation Information

Patent Citations

  • Non-vacuum preparation method of light absorption layer of copper indium gallium sulfur selenium (CIGSSe) thin film solar cell

    CN103602982A

  • Light absorption layer film, preparation method thereof and copper-based thin film solar cell

    CN103928575A

Cited By

  • Copper-vanadium-sulfur-selenium light absorption film and preparation method and application thereof

    CN121449343A

  • Copper vanadium sulfur selenium light-absorbing thin film and preparation method and application thereof

    CN121449343B